Electronic properties of single crystalline diamond surfaces - Ley, Lothar; Ristein, Jürgen; et al. (Carbon, 1999)
Key parameters of the surface electronic structure of diamond (111), such as surface core level shifts, surface state dispersion, band bending, and electron affinity, are presented and discussed. The first actual value for the negative electron affinity of diamond (111):H 1×1 is measured as χ = -1.27 eV. A model is given that describes the variation in χ with hydrogen coverage quantitatively in terms of C-H bond dipoles.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.electr_8